Flavonoid Content and Antioxidant Activity of Brown Rice: Method Temperature and Time - Apriyanto, Mulono; Ariyanto, Anto; Ervayendri; Fitriani, Dita (Open Global Scientific Journal, 2025)
Background: Brown rice contains bioactives, including flavonoids and carotenoids, which function as antioxidants. Polyphenols are flavonoid molecules that are widely found in plant life and have antioxidant properties. Antioxidants can help suppress or prevent oxidation of substrates. The body needs antioxidants to ward off free radicals.Aims: This study evaluated the antioxidant and flavonoid activities of brown rice extract, using ethanol for extraction in an ultrasonic bath. Each of the first and second Erlenmeyer flasks received 150 ml of ethanol for extraction.Methods: An ultrasonic bath operating at 47 kHz and 45 ºC was used for further extraction for either 20 or 30 minutes on the primary flask. The Erlenmeyer jar was also removed at 55 ºC after 20 or 30 minutes. Flavonoid quantifications began with dissolving 10 mg of brown rice extract in ethanol to reach a concentration of 1000 ppm. The content was homogenized until uniform, incubated, and the absorbance measured at 415 nm. To prepare an extract solution from 25 mg of extract, ethanol was added to make a total of 25 ml. The resulting extraction solution contained concentrations of 100, 200, 300, 400, and 500 ppm, with 1 mL of 0.4 mM DPPH solution added to each concentration.Results: Variations in extraction time and temperature did not significantly affect flavonoid levels (p>0.05), increasing extraction temperatures resulted in diminished antioxidant efficacy.Conclusion: The study confirmed the direct correlation between antioxidant capacity and flavonoid concentration, emphasizing that lower extraction temperatures yield better results.